2016
DOI: 10.1016/j.bjm.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

A new alkalophilic isolate of Bacillus as a producer of cyclodextrin glycosyltransferase using cassava flour

Abstract: Cyclodextrin glycosyltransferase (CGTase) catalyzes the conversion of starch into non-reducing cyclic sugars, cyclodextrins, which have several industrial applications. This study aimed to establish optimal culture conditions for β-CGTase production by Bacillus sp. SM-02, isolated from soil of cassava industries waste water lake. The optimization was performed by Central Composite Design (CCD) 2, using cassava flour and corn steep liquor as substrates. The maximum production of 1087.9 U mL−1 was obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The formation of the fisetin/cyclodextrin inclusion complex was also reported in order to improve the property of fisetin ( Zhang et al, 2015 ). CGTase can be found in various bacterial strains such as Bacillus ( Arce-Vázquez et al, 2016 ; de Araújo Coelho et al, 2016 ; Tao et al, 2019 ; van der Veen et al, 2000 ), Pseudomonas ( Jiang et al, 2018 ), and Thermoanaerobacterium ( Leemhuis, Dijkstra & Dijkhuizen, 2003 ). CGTase was used to synthesize various flavonoid glycosides using various flavonoid acceptors such as hesperidin ( Kometani et al, 1994 ), hesperetin ( González-Alfonso et al, 2018 ), naringin ( Kometani et al, 1996 ), epicatechin ( Aramsangtienchai et al, 2011 ) and resveratrol ( Torres et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the fisetin/cyclodextrin inclusion complex was also reported in order to improve the property of fisetin ( Zhang et al, 2015 ). CGTase can be found in various bacterial strains such as Bacillus ( Arce-Vázquez et al, 2016 ; de Araújo Coelho et al, 2016 ; Tao et al, 2019 ; van der Veen et al, 2000 ), Pseudomonas ( Jiang et al, 2018 ), and Thermoanaerobacterium ( Leemhuis, Dijkstra & Dijkhuizen, 2003 ). CGTase was used to synthesize various flavonoid glycosides using various flavonoid acceptors such as hesperidin ( Kometani et al, 1994 ), hesperetin ( González-Alfonso et al, 2018 ), naringin ( Kometani et al, 1996 ), epicatechin ( Aramsangtienchai et al, 2011 ) and resveratrol ( Torres et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to quantitative screening, 5 potent CGTase-producing strains were selected and identified as B. [51,54,55]. Nowadays, RSM is widely reported as an effective statistical technique for designing experiments, building models, evaluating the interactive effects of variables, and pointing the optimum conditions to improve the complex biological processes, especially enzyme production [56−59].…”
Section: Discussionmentioning
confidence: 99%
“…b β-CGTase-H167C was produced with different fermentation temperature with initial pH value at 6.0. c Bacterial strain expressing β-CGTase-H167C was seeded with the indicated inoculum size and the activity of β-CGTase-H167C was detected at each condition. d Different shaking speed was adapted and the production of β-CGTase-H167C was examined Bacillus represented optimum activity at pH 5.0 (Coelho et al 2016). These results indicated that the optimal pH values of CGTase produced by different microbial strains are variable.…”
Section: Initial Phmentioning
confidence: 99%
“…Conventionally, the production of CGTase was achieved by incubating the bacteria with the culture medium that contains essential components for the growth of the microbial. Among the elements in the medium, the carbon and nitrogen sources were obtained with high cost and complex technical issues (Coelho et al 2016). To solve this problem, agro-industrial origins of carbon and nitrogen sources have drawn wide attention (Akindahunsi and Oboh 2003;Brauman et al 1996;Lepiz-Aguilar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation